Effects of pipeline distance, injectivity and capacity on CO2 pipeline and storage site selection. (August 2016) - Wang, Z.; Fimbres Weihs, G.A.; Neal, P.R.; Wiley, D.E.
Highlights: Trade-offs between candidate CO2 sinks with different properties were investigated. Effect of capacity, injectivity and pipeline distance were investigated. A decision tree method is proposed to determine the optimal sink selection. Abstract: Optimising CO2 transport and injection is a challenging issue in Carbon Capture and Storage (CCS), not only because of the complexity of the problem, but also because of timing effects when introducing new sources and/or sinks into the CO2 transport infrastructure. In particular, the effects of storage capacity, injection site location and reservoir properties can propagate to capture and transport costs, affecting the design of the CO2 pipelines. For example, if an injection site does not have enough capacity to store the total amount of CO2 from a capture project, decision makers would need to consider whether to use a larger capacity site, or use the site with small capacity and later switch to a larger capacity site or use both sites. This paper considers the effects of storage capacity, injectivity and distance to source of two sinks on optimal CO2 transport infrastructure design and a static supply of CO2 . Optimal pipeline configurations and sink selection were determined under different combinations of CO2 flow rate, pipeline length and storage site properties. In one scenario, two sinks both have infinite capacity but different injectivities and distances to the emission source. In the other scenario, one sink is relatively small but has a better injectivity or proximity to the emission source. A decision tree approach was developed to provide a quick method for high-level sink selection and pipeline routing for the two scenarios based on the key project parameters including sink capacity, injectivities, pipeline distances and well cost. The scenarios where the decision trees may be useful for simplifying the design of large-scale CO2 pipeline networks have also been analysed.